The over diagnosed COVID-19 infection in an adult patient with foreign body aspiration. (August 2021) - Sharifpour, Ali; Hoseini, Aref; Nekoukar, Zahra; Banimostafavi, Elham Sadat; Fakhar, Mahdi; Soleymani, Mostafa; Zakariaei, Zakaria; Navaeifar, Mohammad Reza; Rsouli, Kimia
Abstract: Introduction and importance: Foreign body aspiration (FBA) in adults may be asymptomatic or symptomatic. Fever and cough are the most common symptoms of Coronavirus infection and other causes of pneumonia. Regardless of the etiology of pneumonia, the first step in the treatment of FBA-associated pneumonia is to remove the foreign body from the airway. Case presentation: A 32-year-old man was referred to our emergency department on October 26, 2020 with shortness of breath (SOB) and a cough. He was referred to the medical center with clinical suspicion of Coronavirus disease-19 (COVID-19), and his disease was treated considering COVID-19. Based on the persistence of his symptoms after discharge, he was referred to the hospital again, and the presence of a foreign body was confirmed by a rigid bronchoscopy, which was then removed. Clinical discussion: Our patient did not remember any history of aspirating solid particles, choking, or any other high-risk conditions associated with aspiration. Also, he had no symptoms with the exception of cough and SOB before the first admission. It means that asymptomatic FBA can be tolerated and go undiagnosed, particularly in adults, and manifests as a secondary complication, such as pneumonia. Conclusion: The FBA and other causal agents may mimic COVID-19 pneumonia. Consequently, FBA should be included in the COVID-19 differential diagnosis. Highlights: The over diagnosed COVID-19 infection in an adult patient with foreign body aspiration. FBA and other causal agents may mimic COVID-19 pneumonia. Consequently, FBA should be included in the COVID-19 differential diagnosis. The taking comprehensive history, physical examination and purposeful paraclinical assessments helps to make the best decision for management of the patients.